2017
DOI: 10.1007/s00784-017-2257-1
|View full text |Cite|
|
Sign up to set email alerts
|

Cone beam computed tomography and ultrasonography imaging of benign intraosseous jaw lesion: a prospective radiopathological study

Abstract: US provides useful information about intraosseous jaw lesions and can be used with CBCT to image such lesions caused by buccal cortical thinning or perforation. Clinicians can take this information into consideration when evaluating intraosseous jaw pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 30 publications
0
25
0
2
Order By: Relevance
“…Second, the study of Bayrakdar et al in 2018, in agreement with our study, showed no significant differences between US and CBCT in the mesiodistal and anteroposterior dimensions, but a significant difference in the superoinferior dimension. 26 As shown in Table 2 , the values of all dimensions after 6 months on US images were lower than the values obtained from CBCT images. This can be explained by the ability of US to show healing sites starting only 6 weeks after the beginning of the healing process.…”
Section: Discussionmentioning
confidence: 73%
“…Second, the study of Bayrakdar et al in 2018, in agreement with our study, showed no significant differences between US and CBCT in the mesiodistal and anteroposterior dimensions, but a significant difference in the superoinferior dimension. 26 As shown in Table 2 , the values of all dimensions after 6 months on US images were lower than the values obtained from CBCT images. This can be explained by the ability of US to show healing sites starting only 6 weeks after the beginning of the healing process.…”
Section: Discussionmentioning
confidence: 73%
“…Many studies have used US to evaluate intraosseous lesions, principally in terms of lesional contents, margins, and vascularity (1,2,(8)(9)(10)(11) Lauria et al (1) compared the US and histopathological findings of 72 intraosseous jaw lesions. US revealed lesional contents prior to surgery (1) .…”
Section: Discussionmentioning
confidence: 99%
“…US is indicated for pregnant and pediatric patients, being simple, painless, repeatable, non-invasive, and economical. US provides useful information on intraosseous jaw lesions (1,2,(8)(9)(10)(11) .…”
Section: Introductionmentioning
confidence: 99%
“…Ayrıca baş ve boyun bölgesindeki inflamatuar yumuşak doku lezyonlarının, neoplazilerin, kemik içi patolojilerin, tükürük bezlerindeki akut inflamasyon, kist, tümör ve apse varlığında ultrasonografi, başvurulan bir görüntüleme yöntemidir. 16,17 KIBT, geleneksel iki boyutlu tekniklerin aksine multiplanar düzlemlerde yapıların üç boyutlu görüntülerini oluşturmaktadır. Bilgisayarlı tomografiye oranla daha düşük radyasyon dozu, görüntüde daha az bozulma ve daha düşük maliyete sahip olması da KIBT'ın diş hekimliğinde kullanımını yaygınlaştıran avantajlarındandır.…”
Section: Tepeklinikunclassified